Development and validation of small animal models for onchocerciasis and loiasis microfilaricide discovery - Ayiseh, Rene Bilingwe; Mbah, Glory Enjong; Monya, Elvis; Ndi, Emmanuel Menang; Sakanari, Judy; Lustigman, Sara; Cho-Ngwa, Fidelis (PLOS Neglected Tropical Diseases, 2023)
Author summary Onchocerciasis (river blindness) caused by the filarial worm Onchocerca volvulus is a severe skin disease and affects the eyes leading to vision loss. Drugs that are effective against O. volvulus should be ineffective against another filarial worm Loa loa, as severe adverse events has been reported in treated co-infected individuals. Thus, animal models are needed to screen for compounds effective against onchocerciasis but not against the Loa loa microfilariae (mf). O. ochengi mf from cattle skin and L. loa mf from human blood were used to infect BALB/c mice and Mongolian gerbils, and ivermectin (IVM) was used for model validation. O. ochengi mf survived both animals and treatment with IVM significantly reduced the number of mf. In a BALB/c L. loa mf model, IVM significantly reduced mf in treated mice compared to the untreated. L. loa mf survived in peritoneum of gerbils. A gerbil co-injection model (with both O. ochengi and L. loa mf) was developed and both mf survived for up to 50 days in this model. In conclusion, we have developed two immunocompetent small animal models for onchocerciasis and loiasis that can be used for microfilaricide discovery.